Pengaruh Kepuasan Kerja dan Motivasi Terhadap Loyalitas Pegawai Di Toko Prima Elektronik Cabang Kupang - Isaskar Eliut Sanam; Wuake Andrea (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study aims to examine the influence of job satisfaction and motivation on employee loyalty at the Prima Elektronik Store, Kupang Branch. The background of this study is the importance of maintaining employee loyalty in an increasingly competitive environment. This study used a quantitative approach by surveying 50 employees as a full sample of saturation sampling. Data were analyzed using multiple linear regression analysis to test the joint and partial effects between variables. The results showed that job satisfaction and motivation have a positive and significant effect on employee loyalty both partially and simultaneously. The t-test results show a significance value of each independent variable (job satisfaction and motivation) <0.05, the F-test results show a significance value of 0.000, and the calculated F> F table indicates a significant joint effect. The coefficient of determination (R²) of 0.806 indicates that 80.6% of the variance in employee loyalty can be explained by job satisfaction and motivation. These results confirm that to increase employee loyalty, companies need to create a conducive work environment and provide continuous motivation in the form of tangible and intangible. This study is expected to provide a strategic basis for more effective human resource management in electronic retail.